Maximal Oxygen Uptake Equations to Discriminate the Cardiometabolic Risk in Colombian Children and Adolescents: The Fuprecol Study - Garcia-Hermoso, A (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Sin Resumen Disponible